2013
DOI: 10.1177/2156759x1201600501
|View full text |Cite
|
Sign up to set email alerts
|

A High School Counselor's Leadership in Providing School-Wide Screenings for Depression and Enhancing Suicide Awareness

Abstract: The prevalence of mental health issues and suicidal thoughts and actions among school-aged children and adolescents is a serious issue. This article examines the scope of the problem nationwide and provides a brief overview of the literature regarding the effectiveness of school-wide screening programs for depression and suicide risk. The authors describe a suicide prevention program that has been implemented by the first author (a high school counselor in Minnesota) that combines classroom guidance, screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…The current status quo is lacking (Barrio Minton & Pease‐Carter, 2011), and new counselors feel underprepared to address suicide (Liebling‐Boccio & Jennings, 2013). After graduation, professional counselors will be directly serving people at risk of suicide, and by virtue of their position as mental health experts, they will also be called upon to help their communities respond to the issue of suicide (Erikson & Abel, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current status quo is lacking (Barrio Minton & Pease‐Carter, 2011), and new counselors feel underprepared to address suicide (Liebling‐Boccio & Jennings, 2013). After graduation, professional counselors will be directly serving people at risk of suicide, and by virtue of their position as mental health experts, they will also be called upon to help their communities respond to the issue of suicide (Erikson & Abel, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although referral for inpatient treatment may seem a responsible choice by a school counselor who is often forced to work under systemic constraints (Erikson & Abel, 2013), evidence suggests that the action of referral rather than intervention is not optimal. Being referred can contribute to an at‐risk student’s isolation from the school system and add to a sense of being burdensome to others.…”
Section: Si Training For Counselors‐in‐trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention programs can empower students and staff by describing how to respond to a student overtly expressing suicidal ideations or behaviors (Doan, Roggenbaum, & Lazear, 2003). Erickson and Abel (2013) implemented a school-wide prevention program that included depression screenings and reported positive results. They found that 10% of the students screened were at risk for depression.…”
Section: The Role Of Schools and School Counselorsmentioning
confidence: 99%
“…Junhke, Granello, and Granello, have framed the rising rates of suicide in adolescents as a public health concern and one in which schools can play a large preventative role (2011). When considering the professionals qualified to lead suicide prevention efforts, school counselors are in the ideal position to work with students, identify warning signs, and inform parents (Erickson & Abel, 2013;King, Price, & Telljohann, 2000;Ward & Odegard, 2011).…”
Section: Introductionmentioning
confidence: 99%